2019
DOI: 10.1097/dcr.0000000000001228
|View full text |Cite
|
Sign up to set email alerts
|

Low Anterior Resection Syndrome and Quality of Life After Sphincter-Sparing Rectal Cancer Surgery: A Long-term Longitudinal Follow-up

Abstract: BACKGROUND: Despite low anterior resection syndrome being a well-known consequence of sphincter-preserving rectal cancer surgery, the long-term effect on bowel function and quality of life is not fully understood. OBJECTIVE: This study aimed to elucidate whether symptoms of low anterior resection syndrome change over time and if the correlation to quality of life is equivalent when measured at 2 time points. DESIGN: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
119
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(133 citation statements)
references
References 20 publications
9
119
0
5
Order By: Relevance
“…Differently from our study, Gadan et al did show the long-term negative effect of ileostomy formation on bowel function 13 . Similarly to our study, Pienowski et al found in a long-term preoperative chemoradiotherapy, younger age and low level of the tumour were the risk factors of having LARS, and having major LARS 14 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Differently from our study, Gadan et al did show the long-term negative effect of ileostomy formation on bowel function 13 . Similarly to our study, Pienowski et al found in a long-term preoperative chemoradiotherapy, younger age and low level of the tumour were the risk factors of having LARS, and having major LARS 14 .…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge there are only five studies investigating long-term LARS following rectal surgery and influence it has on patients’ daily life using validated LARS score 10 14 . These studies showed that LARS was found in 47.5% to 90% of patients following rectal cancer surgery in long-term period.…”
Section: Introductionmentioning
confidence: 99%
“…These recent studies have indicated that there is a need for improved LARS education for clinicians 25 26. There is now evidence that both the distribution of patients within different LARS groups (minor and/or major) and the impact of LARS on QoL do not change over time 30. According to recent studies,31 nearly 50% of patients still experience major LARS 13 to 15 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Sphincter preservation and restoration of intestinal continuity is feasible in up to 80% of patients with rectal cancer, thereby avoiding a stoma. Nonetheless, 60–70% of patients will experience a more or less permanent set or combination of symptoms, collectively known as low anterior resection syndrome (LARS), that range from faecal incontinence to intestinal dysfunction in the form of erratic defaecatory patterns, faecal urgency and obstructed defaecation . This syndrome has a negative impact on quality of life and patients become toilet dependent .…”
Section: Introductionmentioning
confidence: 99%